A rare presentation of pleomorphic carcinoma of lung mimic empyema - Yang, Kuo-Ming; Tang, En-Kuei; Goan, Yih-Gang; Tseng, Yen-Chiang (Annals of Translational Medicine, 2018)
Pleomorphic carcinoma (PC) of lung, a rare malignant lung tumor, is predominated in male smokers with over 65 years of age. The clinical presentations of PC are various including chest pain, cough, and dyspnea and so on. Asymptomatic patients have been also reported. In our case, a female non-smoker with middle age, who initially developed symptoms like empyema was diagnosed advanced PC. Poor progression occurred in this patient within one month from diagnosis to expiration. The lesson from this case is that malignancy of lung such as PC could not be excluded if a patient develops unmanageable empyema.